Effects of annealing time and temperature on the crystallinity and heat resistance behavior of injection‐molded poly(lactic acid). Issue 3 (10th August 2012) - Srithep, Yottha; Nealey, Paul; Turng, Lih‐Sheng
Abstract The effects of annealing time and temperature on the crystallinity of injection‐molded poly(lactic acid) (PLA) were investigated using differential scanning calorimetry and wide‐angle x‐ray diffraction. Differential scanning calorimetry, tensile test, and dynamic mechanical analysis showed that an increase in crystallinity in the PLA parts from the annealing treatment offers several benefits such as a higher glass transition temperature, better heat resistance, and greater storage modulus and tensile strength. Based on the experimental data, the degree of crystallinity, annealing time, and annealing temperature were found to closely follow the time–temperature superposition relationship. Namely, a master curve could be constructed based on either the Williams–Landel–Ferry equation or the Arrhenius relationship by shifting the crystallinity isotherms in the logarithmic scale horizontally along the log‐time axis. This relationship provides a quantitative guideline for annealing postinjection‐molded PLA parts to improve the heat resistance and mechanical properties. An increase of over 17% and 26% in tensile strength was achieved at an annealing temperature of 80°C for 30 min and 65°C for 31 h, respectively. POLYM. ENG. SCI. 2013. © 2012 Society of Plastics Engineers